Lum and Abner : Rural America and the Golden Age of Radio - Hall, Randal L., 1971- (Book collections on Project MUSE., 2007)
In the 1930s radio stations filled the airwaves with programs about rural Americans struggling through the Great Depression. One of the most popular of these shows was Lum and Abner, the brainchild of two young businessmen from Arkansas. Chester ""Chet"" Lauck and Norris ""Tuffy"" Goff based Pine Ridge, the community they created on the air, on the hamlet of Waters, Arkansas. The title characters, who are farmers, local officials, and keepers of the Jot 'Em Down Store, manage to entangle themselves in a variety of hilarious dilemmas. In Lum and Abner: Rural America and the golden Age of Radio.